IMPACT OF LADY HEALTH WORKERS ON THE CONTRACEPTIVE PREVALENCE RATE IN DISTRICT MARDAN - Nisar, Shahana; Khan, Maria; Nisar, Uzma (Journal of Ayub Medical College Abbottabad, 2020)
Background: Pakistan being the 6th populous country with a population of 207,774,520, and a growth rate of 2.6%, if left unchecked can reach 335 million by 2050. The total demand of family planning in Pakistan is 55% while the contraceptive prevalence rate is 35% with an unmet need for family planning is 20%. Methods: The contraceptive prevalence rate and frequently used contraceptive method in an area with Lady Health Worker services versus an area without Lady Health Worker services of union council Pat Baba were compared over a period of 6 months. 322 households were selected, 161 from LHW covered and 161 from LHW uncovered area of union council Pat Baba District Mardan. Results: The knowledge of contraceptive methods was 98.1% in the women of covered area and this knowledge was 90.1% in the uncovered area in union council Pat Baba. The source of information for the women in the covered area was mostly LHWs 87% and in uncovered area 25.5% of the women were informed by the LHWs, followed by elderly family members 7.5% in the covered, and 37.9% of the women in uncovered area. The contraceptive prevalence rate was 59% in covered areas and in uncovered areas it was 51.6%. The most frequently used contraceptive method in covered area was condom 16.8% and in the uncovered area it was withdrawal method 26.1%. Conclusions: There was a significant association between the LHWs presence on knowledge scores and contraceptive prevalence rate. Keywords: Contraceptive; Lady Health Worker; Family planning